2020
DOI: 10.1002/ecs2.3282
|View full text |Cite
|
Sign up to set email alerts
|

Spawning salmon density influences fruit production of salmonberry (Rubus spectabilis)

Abstract: Spawning salmon density influences fruit production of salmonberry (Rubus spectabilis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 59 publications
(91 reference statements)
3
10
0
Order By: Relevance
“…The addition of marine-derived nutrients increased seed set in yarrow in the third and final year of the study. This is consistent with prior work on riparian plant species such as salmonberry, which produces a higher abundance of berries per plant on streams with larger returns of chum salmon [ 19 ]. Other work on the effect of nitrogen fertilization has shown that seed output may take several seasons of fertilization to respond [ 50 ], or may not respond to resource supplementation at all [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The addition of marine-derived nutrients increased seed set in yarrow in the third and final year of the study. This is consistent with prior work on riparian plant species such as salmonberry, which produces a higher abundance of berries per plant on streams with larger returns of chum salmon [ 19 ]. Other work on the effect of nitrogen fertilization has shown that seed output may take several seasons of fertilization to respond [ 50 ], or may not respond to resource supplementation at all [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…Effects on terrestrial communities include the alteration of plant, insect, and bird community structure and diversity [ 15 17 ]. Effects on individuals can be seen in birds, where salmon subsidies can influence male habitat selection, behaviour and territory size [ 18 ], and riparian plants, where salmon subsidies can increase stomatal density and fruit production [ 19 , 20 ]. Much of the recent work on salmon subsidies in terrestrial habitats has been necessarily observational, with a few notable exceptions [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsidies fluctuate in amount, quality, timing, and duration, eliciting variable effects on ecosystems (Piovia‐Scott et al, 2019; Subalusky & Post, 2019). In one study, larger amounts of spawning salmon significantly increased riparian per‐shrub berry production in Canadian streams (Siemens et al, 2020), which potentially affects avian and mammalian consumers (Traveset & Willson, 1998). Another study found that changing the seasonal timing of subsidy addition to plants resulted in a shift from bottom‐up effects for herbivores to top‐down suppression by predators (Gratton & Denno, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The list of interactors is certainly incomplete due to the limited scope of our field surveys. Other types of interactions that have not yet been studied include responses to salmon‐derived nutrients among riparian plants (e.g., Hocking & Reynolds, 2011; Siemens et al, 2020), consumption of juvenile salmon and salmon eggs by forest birds (e.g., Tonra et al, 2016), the transport of salmon‐derived nutrients into terrestrial food webs through the emergence of stream insects (e.g., Francis et al, 2006), microbial interactions (discussed below), and bioturbation effects due to disturbance of the streambed (e.g., Moore & Schindler, 2008). Moreover, the prevalence of these interactions likely varies spatially and temporally due to variation in physical and biological characteristics of ecosystems.…”
Section: Discussionmentioning
confidence: 99%